Blackfaced white: rasowe przypadki negatywu - Kanicki, Witold (Artium Quaestiones, 2018)
In her essay on the involvement of photography in the system of racial division, Tanya Sheehan (“Comical Conflations: Racial Identity and Science of Photography,” Photography & Culture, vol. 4, no. 2, 2011: 133-156) focused her attention on common comparisons of the photographic negative to the Negroid race. Such a tendency may imply a claim that the negative is racist; once connected, just as African Americans, with pejorative features. The negative picture, different from reality as such but above all negating a realistic (positive) tradition in art, because of being different (other) can be considered wrong or inferior to the positive so that it must be hidden or even destroyed. In such a context, the present paper focuses on the relationship between the photographic negative and the question of race. Although apparently the reversal of the color of skin might result in a racial transformation of the photographed whites, the artistic practice of the 20th and 21st centuries demonstrates that quite often the reversed color does not necessarily mean a change of race. What is more, the negative has been used to oppose by artistic means the simplifying polarization of society. Such avant-garde photographers as Hans Bellmer, Man Ray, and Alexandr Rodchenko used the inversion of tone in their works critiquing colonial and racist stereotypes. Contemporary artists use the negative convention to subvert the dominant positive, realism, light, day, the white male, and other concepts associated with one of the poles constituting the binary value system. Painting one’s face black, in the 19th century used in evidently racist performances called “minstrel shows,” may now convey a positive message.